Seed Storage Behaviour of Tinospora cordifolia - C ANILKUMAR; CR CHITRA; S BINDU; G RAJKUMAR (Seed Research, 2026)
Studies were conducted on Tinospora cordifolia, [Indian tinospora or Guduchil, a highly sought-after medicinal plant and fast disappearing species from wild habitat, for analyzing the seed storage behaviour for the purpose of ex-situ conservation; keeping bio diversity conservation in view. Sensitivity of seeds dried to different moisture levels, with respect to germinability, revealed desiccation/drying tolerance up to 8.5% moisture. Apart from this, chilling sensitivity to sub zero temperature also indicated intermediate nature. Control seeds with 16.9% moisture recorded viability for two weeks whereas, seeds dried to 7.8% moisture stored at 20°C retained 80% viability for six months.